A Late Geometrie Grave-Scene Influenced by North Syrian Art - Ahlberg, Gudrun (1967)
= Skrifter utgivna av Svenska Institut i Athen, 4°, XII/Acta Instituti Atheniensis Regni Sueciae, series in-4°, XII; occurs on a series of Attic Late Geometric vases; two persons seated opposite each other at a table or table-like structure, handling objects of specific character; compares reliefs from Zincirli, Maraş, Malatya and the seal VA 7827.